Pengembangan Media Buku Bantuan Diri untuk Memberikan Pemahaman Bahaya Merokok - Vania Aprilo Livia Hutabarat; Raudah Zaimah Dalimunthe; Putri Dian Conia (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The study aims to develop self-help book media to understand the dangers of smoking. The method used is Research and Development (R&D) with the development of ADDIE Analysis, design, development, implementation and evaluation). The evaluation was carried out by validators of media experts, materials, language experts and expert practitioners. Based on these data, the results of the evaluation of the validity of media experts were 85%, material experts were 80%, the percentage obtained from language experts was 96.4% and the percentage from practitioners was 84.6%. The average feasibility result was 86.5% with the category "feasible" for use. Self-help books can be used independently and packaged systematically. Limited trials were conducted on 19 guidance and counseling students from the 2023 and 2024 intakes. So it can be concluded that the development of self-help books to provide an understanding of the dangers of smoking is a self-help book that is feasible to implement.